SINERGI PEMERINTAH DAN PERUSAHAAN PADA AKTIVITAS CSR DALAM RANGKA MENGHADAPI MEA - Kokom Komariah; Evi Novianti; Hanny Hafiar; Ari Agung Prastowo (Jurnal Kawistara, 2017)
Corporate Social Responsibility activities ideally be felt by the West Bandung Regency, where The West Bandung Regency has now transformed into an industrial area. This change of course, like the two-edged sword, the meaning is the presence of the company is actually able to provide changes in the economy for local communities, in an effort to prepare for the MEA, but on the other hand an industrial presence in West Bandung Regency giving new homework in terms of environmental management and the company's contribution to increasing local revenues of West Bandung regency. Whereas CSR is expected to become one of the company's contributions to improving the competitiveness of West Bandung Regency society. In other words, the company's contribution through Corporate Social Responsibility activities, become the hope of West Bandung regency government in building the human resources of competitive and independent and prosperous. Therefore, this study aims to dig deeper into the synergy of government and companies on CSR activities in order to face the MEA. This research is using qualitative descriptive method through data collection techniques of interviewing and observation. The results of this research indicate that in practice between the government and companies there are communication problems, therefore it is necessary to build appropriate communication models between the government and the companies as well as the community called tripartite corporate social responsibility so that corporate social responsibility activities better planned, targeted and sustainable.